2000
DOI: 10.1034/j.1600-0854.2000.010407.x
|View full text |Cite
|
Sign up to set email alerts
|

Coatomer Vesicles are not Required for Inhibition of Golgi Transport by G‐Protein Activators

Abstract: The G-protein activators guanosine 5%-O-(3-thiodiphosphate) (GTPgS) and aluminum fluoride (AlF) are thought to inhibit transport between Golgi cisternae by causing the accumulation of nonfunctional coatomer-coated transport vesicles on the Golgi. Although GTPgS and AlF inhibit transport in cell-free intra-Golgi transport systems, blocking coatomer vesicle formation does not. We therefore determined whether inhibition of in vitro Golgi transport by these agents requires coatomer vesicle formation. Depletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…This apparent discrepancy may arise from the fact that GTP analogs and AlF 4 inhibit different cellular targets. For example, it has been suggested that the AIF-sensitive component in vesicle transport may not be a GTP-binding protein (21). Indeed, AlF 4 is known to inhibit other phosphoryl transfer reactions involved in vesicle transport, such as phospholipase D activity (27,34).…”
Section: Discussionmentioning
confidence: 99%
“…This apparent discrepancy may arise from the fact that GTP analogs and AlF 4 inhibit different cellular targets. For example, it has been suggested that the AIF-sensitive component in vesicle transport may not be a GTP-binding protein (21). Indeed, AlF 4 is known to inhibit other phosphoryl transfer reactions involved in vesicle transport, such as phospholipase D activity (27,34).…”
Section: Discussionmentioning
confidence: 99%
“…Unfractionated and reconstituted cytosols had identical capacity to inhibit transport in the presence of the non-hydrolysable analog of GTP, GTP␥S, indicating that ARF function was reconstituted (27). COPI-depleted cytosol was prepared by immunodepletion with the COPI monoclonal antibody, CM1A10 (26). Cytosol was incubated twice with either CM1A10 protein G beads to produce COPI-depleted cytosol or with c-Myc monoclonal antibody (9E10) protein G beads to produce mock-depleted cytosol.…”
Section: Methodsmentioning
confidence: 99%
“…A straightforward explanation for this cytosol requirement might be that the steady-state level of free intermediates is dependent on the amount of Golgi coat proteins available to produce them. COPI is the dominant coat protein associated with Golgi vesicles, and depletion of COPI from cytosol essentially eliminates the production of coated vesicles on cisternae during an in vitro incubation (26). Paradoxically, COPI depletion does not inhibit transport in these in vitro assays (26).…”
Section: Enzyme Intermediates Formed In Vivo and In Vitro Are Indistimentioning
confidence: 99%
See 2 more Smart Citations